Strategi Pengelolaan BUMDes Dalam Bidang Kesehatan Pada Pemberdayaan Masyarakat - Aminuddin Aminuddin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
This study aims to determine the strategies for empowering rural communities by developing village-owned enterprises through health services. This research uses descriptive qualitative research. Namely research conducted using a natural setting with the intention of interpreting a phenomenon that occurs and is carried out by involving various existing methods. Data collection techniques used through literature study or review of various sources or literature related to the problem under study. An independent village as part of the ideals of national development is hampered by various problems that arise in its realization. One of the most dominant things, namely in the economic sector and social sector. One effort that can alleviate health problems and empower rural communities is the establishment of a business institution called the Village-Owned Usha Agency (BUMDes). However, in the business activities carried out by BUMDes, various problems have arisen, namely (a) lack of community participation in BUMDes management; (b) the village government does not maximally empower the community to develop.